Analisis Kadar Kalsium Dari Maman Dan Fermentasi Maman (Cleome gynandra L) - Fathul Jannah; Syafrisar Meri Agritubella; Ira Oktaviani RZ; Rahimatul Uthia (JURNAL FARMASI DAN MAKANAN, 2024)
Calcium is an important micronutrient that helps prevent stunting. It plays a crucial role in bone growth. Maman (Cleome gynandra L.) is a local plant that grows in the Riau province and is used by local people as a fermented food. To utilize this local plant, it is necessary to analyze its nutrients, including calcium levels. Calcium analysis was carried out using a quantitative descriptive method with an atomic absorption spectrophotometer. Validation of the atomic absorption spectrophotometry method yielded a correlation coefficient (r) of 0.9997, with calcium levels in maman leaves and fermented maman being 3132.33 mg/g and 1976.31 mg/g, respectively.